2019
DOI: 10.1080/17499518.2019.1652918
|View full text |Cite
|
Sign up to set email alerts
|

On characteristic values and the reliability-based assessment of dykes

Abstract: A case study involving the assessment and re-design of an existing dyke, founded on a layered soil, has compared deterministic analysis based on 5-percentile property values and a reliability-based random finite element analysis consistent with the requirements of Eurocode 7. The results show that a consideration of the spatial nature of soil variability generally leads to higher computed factors of safety and, for those dyke sections requiring remedial action, to more economic designs. Back-figured characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…One solution is to use a simplified approach for calculating the value of X k , which can then, after application of partial factors, be used in deterministic analyses to obtain reliability-based values of F. For example, Dutch engineering practice calculates F for dykes by using the 5 percentile of either the underlying soil property distribution or a distribution which takes some account of spatial variability by using simplified variance reduction. Recently, Hicks et al (2019) showed how RFEM can be used (with or without partial factors) to directly determine reliability-based factors of safety, without having to explicitly derive the characteristic values. Although this method is computationally intensive, it removes the need to determine X k , is completely general, and automatically accounts for both variance reduction and the reduced mean due to weaker zones.…”
Section: Characteristic Values and Design According To Ec7mentioning
confidence: 99%
See 4 more Smart Citations
“…One solution is to use a simplified approach for calculating the value of X k , which can then, after application of partial factors, be used in deterministic analyses to obtain reliability-based values of F. For example, Dutch engineering practice calculates F for dykes by using the 5 percentile of either the underlying soil property distribution or a distribution which takes some account of spatial variability by using simplified variance reduction. Recently, Hicks et al (2019) showed how RFEM can be used (with or without partial factors) to directly determine reliability-based factors of safety, without having to explicitly derive the characteristic values. Although this method is computationally intensive, it removes the need to determine X k , is completely general, and automatically accounts for both variance reduction and the reduced mean due to weaker zones.…”
Section: Characteristic Values and Design According To Ec7mentioning
confidence: 99%
“…Figure 2 shows the idealised dyke cross-section analysed by Hicks et al (2019), which is the same as that used previously by Kames (2015) in limit equilibrium slope stability analyses based on 5-percentile characteristic values. Table 2 lists, for each soil layer, the mean, 5 percentile and coefficient of variation (COV) of the shear strength parameters (cohesion c′ and tangent of friction angle ϕ′), which were assumed to follow log-normal distributions, as well as the unit weight γ, which was assumed to be deterministic (Kames, 2015).…”
Section: Analysis Of Dyke Cross-sectionmentioning
confidence: 99%
See 3 more Smart Citations